Smoke - Hopkins, Ellen (New York : Margaret K. McElderry Books, 2013)
After the death of her abusive father and loss of her beloved Ethan and their unborn child, Pattyn runs away, desperately seeking peace, as her younger sister, a sophomore in high school, also tries to put the pieces of her life back together.
Sequel to: Burned.
Keywords: Novels in verse; Grief -- Juvenile fiction; Emotional problems -- Juvenile fiction; Sisters -- Juvenile fiction; Runaways -- Juvenile fiction; Mormons -- Juvenile fiction